The Ethics of Translational Audiology - Aleksandra Bendowska; Roksana Malak; Agnieszka Zok; Ewa Baum (Audiology Research, 2022)
Translational research moves promising primary research results from the laboratory to practical application. The transition from basic science to clinical research and from clinical research to routine healthcare applications presents many challenges, including ethical. This paper addresses issues in the ethics of translational audiology and discusses the ethical principles that should guide research involving people with hearing loss. Four major ethical principles are defined and explained, which are as follows: beneficence, nonmaleficence, autonomy, and justice. In addition, the authors discuss issues of discrimination and equal access to medical services among people with hearing loss. Despite audiology’s broad field of interest, which includes evaluation and treatment of auditory disorders (e.g., deafness, tinnitus, misophonia, or hyperacusis) and balance disorders, this study focuses primarily on deafness and its therapies.